A Case Report of Takayasus Arteritis (Medicine Today, 2013)
Takayasus arteritis, or pulseless disease is a rare, idiopathic, chronic granulomatous vasculitis that affects aorta and its major branches. This report describes a 57- year-old man who presented with gradual loss of vision, syncopal attack and arm claudication. His ocular findings suggested bilateral ocular ischemic syndrome. He was later diagnosed as having Takayasus disease.DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15013 Medicine Today 2012 Vol.24(2): 79-81